El uso del software HistCite para identificar artículos significativos en búsquedas por materias en la Web of Science - Wulff Barreiro, Enrique (Documentación de las Ciencias de la Información, 2007)
HistCiteTM is a large-scale computer tool for mapping science. Its power of visualization combines the production of historiographs on the basis of the analysis of co-citations of documents, with the use of bibliometrics specific indicators. The objective of this article is, to present the advantages of the new bibliometrics configuration of HistCiteTM (2004) when identifying articles to analyze the histograms that produces HistCiteTM, in terms of cumulative advantage and aging of the citations to do a comparative study of the results of HistCiteTM, in its indicators of amplitude and recognition. Also is examined its treatment of the sampling problems, by formalizing the question of Kendall.